Assessing Indian corporate ecological intelligence: a case study of selected companies / MSV. Prasad and B. Sandhya Sri - MSV, Prasad; B., Sandhya Sri (Accounting Research Institute (ARI), 2012)
The main objective of this paper is to establish the ecological intelligence vis-à-vis the less ecological intelligence of Indian companies and to analyze to what extent ecological intelligence influences the adoption of ecological accounting and reporting practices among Indian companies. This research began with the formulation of two hypotheses and based on them, two models were proposed. Stepwise regression was applied to test the two models of ecological intelligence and non-ecological intelligence to explore and establish the ecological intelligence of select companies. Chi-square test showed that the adoption of ecological accounting procedures was significantly higher in ecologically intelligent industry groups than in non-ecologically intelligent industry groups. Stepwise regression method justified the two hypotheses. The paper examines the ecological intelligence of the industry as a factor associated with the adoption of ecological accounting and control procedures. The results of the study highlight that firms should move towards triple bottom line reporting and also show how the traditional accounting information system needs to be modified to face this challenge in developing countries. The paper shows how readily ecological intelligence culture can be adopted by Indian companies.